RESEARCH OF DIRECTIONS OF DEVELOPMENT OF LAND MANAGEMENT DOCUMENTATION TAKING INTO ACCOUNT OF MODERN LEGAL REQUIREMENTS: Array - Nesterenko, S.; Radzinska, Y.; Kasyanov, V.; Holovachov, V.; Frolov, V. (Municipal economy of cities. Series: «Economy science», 2022)
In recent years, there has been an increase in activity in the field of land and the acquisition of land ownership. In order to properly establish the boundaries of plots for any needs, it is necessary to create a project for the allocation of land. The Law of Ukraine "On Land Management" clearly prescribes the rules and procedures for creating such projects. The law defines the land management project. A land management project is a set of documentation, which includes technical, economic and technical types of documentation that provide a justification for the necessary measures for the use and protection of land that must be performed under this project. There is a need to determine in more detail the components of land management projects, the grounds for their development, land management documentation, the formation of projects for urban planning needs and other types of land management activities. At the same time, the issue of collecting and systematizing cadastral data, forming a cadastral system and access of different groups of users to it at different levels of interaction remains unaccounted for. Modern legal aspects of land management documentation development, etc. need more detailed analysis. The aim of the article is to study the principles of development of land management documentation for various purposes, taking into account modern regulatory requirements. The paper analyzes modern approaches to the development of land management documentation, analyzes the components of land management projects. The bases of development of the documentation on land management are defined, questions of formation of projects for town-planning needs are investigated. The issues of collection and systematization of cadastral data, formation of cadastral system and access of different groups of users to it at different levels of interaction are analyzed. Issues of regulatory and legal support for the creation of land management documentation have been studied. The issues considered in the study will provide a clearer understanding of the concept of land management project, land management documentation, cadastral data, land use formation and more.